Youth Empowerment in Kalidawir Village - Muhammad Alif Rafifuddin; Isna Fitria Agustina (Universitas Muhammadiyah Sidoarjo, 2021)
Community empowerment is a development strategy as a form of activity to help the community to gain efficiency, make decisions and determine the actions to be taken. The form of community empowerment can involve youth in activities at the village level. The purpose of this study was to explain and analyze youth empowerment in Kalidawir Village, Tanggulangin District, Sidoarjo Regency. This study focuses on one theory of empowerment, namely Doing, Effects, Association. The method used is qualitative descriptive data obtained through observation, documentation, interviews and using sources from books, journals, and policy documents. The results of this study stated that the empowerment of youth in Kalidawir village experienced a change in leadership which resulted in not running optimally and lack of support from the village community for youth in Kalidawir Village.